1999
DOI: 10.1209/epl/i1999-00272-8
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of semiconducting rhenium silicide

Abstract: For the first time, theoretical arguments for the semiconducting properties of the ReSi1.75 phase have been given by means of ab initio linear muffin-tin orbital method (LMTO) calculations. It is shown that the material is indeed a narrow-gap semiconductor with an indirect gap value of 0.16 eV. The first direct transition with appreciable oscillator strength at 0.30 eV is predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…The discussion given here can be implemented to the large theoretical value of the electrical conductivity along [1 0 0]. The calculated thermoelectric power along [0 0 1] is in fairly good agreement with the experimental value above about 650 K. There is a transition region between 330 and 650 K. It is worthwhile to note that E F at the Z direction lies just above the valence band maximum, according to the result of the band calculation [7,8], which implies that the thermoelectric power is positive at low temperatures. As the temperature increases, E F moves to the center of the band gap, leading to our assumption of that…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The discussion given here can be implemented to the large theoretical value of the electrical conductivity along [1 0 0]. The calculated thermoelectric power along [0 0 1] is in fairly good agreement with the experimental value above about 650 K. There is a transition region between 330 and 650 K. It is worthwhile to note that E F at the Z direction lies just above the valence band maximum, according to the result of the band calculation [7,8], which implies that the thermoelectric power is positive at low temperatures. As the temperature increases, E F moves to the center of the band gap, leading to our assumption of that…”
Section: Resultssupporting
confidence: 58%
“…So, one may conclude that this effect is the origin of the high thermoelectric performance along [0 0 1]. According to the band calculation results [7,8], the eigenstate of the valence band maximum at the G point consists of pure d-like states of rhenium (about 90%), and changing the stoichiometry from ReSi 1.75 to ReSi 1.875 and ReSi 2 did not affect the flat character of the highest valence band at the G-Z direction. This indicates that the large effective mass of holes along [0 0 1] is mainly due to the rhenium atoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy can stem from the fact that Göransson [6] using a linear muffin-tin orbital method in the atomic sphere approximation did not perform a full structural optimization. Moreover, a band structure obtained within the atomic sphere approximation could be sensitive to the ratio of the atomic sphere radii of the Ir and Si atoms [13] and to radii of empty spheres [14]. Imai and Watanabe [7] displayed the band diagram along many directions in the Brillouin zone.…”
Section: Band Structurementioning
confidence: 99%
“…Recently, Gottlieb et al [4] and our group [5,6] have shown that, for bulk crystals, the stoic hiometry is ReSi,,,~and a range of monoclinic structures derived from C 1lb structure are observed. First principles calculations using the stoichiometry of ReSi}.7~and the monoclinic structure observed by Gottlieb et al [4] have indeed predicted a semiconducting behavior with an indirect gapof0,16eV [12].…”
Section: Introductionmentioning
confidence: 84%